A spatial framework to explore needs and opportunities for interoperable urban flood management. (17th February 2020) - Dawson, David A.; Vercruysse, Kim; Wright, Nigel
Abstract : Managing current and future urban flood risks must consider the connection (i.e. interoperability) between existing (and new) infrastructure systems to manage stormwater (pluvial flooding). Yet, due to a lack of systematic approaches to identify interoperable flood management interventions, opportunities are missed to combine investments of existing infrastructure (e.g. drainage, roads, land use and buildings) with blue-green infrastructure (e.g. sustainable urban drainage systems, green roofs, green spaces). In this study, a spatial analysis framework is presented combining hydrodynamic modelling with spatial information on infrastructure systems to provide strategic direction for systems-level urban flood management (UFM). The framework is built upon three categories of data: (i) flood hazard areas (i.e. characterize the spatial flood problem); (ii) flood source areas (i.e. areas contributing the most to surface flooding); (iii) the interoperable potential of different systems (i.e. which infrastructure systems can contribute to water management functions). Applied to the urban catchment of Newcastle-Upon-Tyne (UK), the study illustrates the novelty of combining spatial data sources in a systematic way, and highlights the spatial (dis)connectivity in terms of flood source areas (where most of the flood management intervention is required) and the benefit areas (where most of the reduction in flooding occurs). The framework provides a strategic tool for managing stormwater pathways from an interoperable perspective that can help city-scale infrastructure development that considers UFM across multiple systems. This article is part of the theme issue 'Urban flood resilience'.